DEVELOPMENT AND EVALUATION OF A MEDICAL RECORD ED- UCATION SYSTEM USING THE WATERFALL MODEL WITH ISO 9126/25010 QUALITY MAPPING - Wahyu Wijaya Widiyanto; Yayak Kartika Sari; Edy Susanto (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This study aims to develop and evaluate a Medical Record Education System designed to enhance students’ digital competence in managing electronic medical records (EMRs). Addressing the gap between the- oretical learning and practical application in health informatics educa- tion, the system was developed using the Waterfall model and evaluated through the ISO 9126 software quality framework. A Research and De- velopment (RD) approach was applied at Politeknik Indonusa Surakarta involving 30 final-year students of the Health Information Management program. Data collection included observation, ISO 9126-based ques- tionnaires, and in-depth interviews, analyzed using descriptive and the- matic techniques. The results showed significant improvement in student performance, with pretest–posttest scores increasing from 64.5 to 86.2 after a two-week system trial. The system comprises interactive modules such as patient data entry, diagnosis coding, and auto-report generation. Expert evaluation produced high scores for usability (4.6), functionality (4.4), reliability (4.2), and efficiency (4.3), confirming both educational value and technical feasibility. These findings highlight the role of struc- tured development and quality assessment models in instructional in- novation. The system not only improves learning outcomes but also provides a replicable model for embedding digital transformation into vocational healthcare education.